Dynamics of clomazone formulations combined with sulfentrazone in sugarcane (Saccharum spp.) straw - Tropaldi, Leandro [UNESP] (2021)
Herbicide formulations can alter the herbicide performance, affecting the application safety and weed control efficiency. Thus, the objective of this work was to compare the dynamics of clomazone herbicide applied single and combined with sulfentrazone on sugarcane (Saccharum spp.) straw. Laminated polypropylene containers filled with sugarcane straw (10 t ha−1) were subjected to two clomazone formulations (microencapsulated and conventional formulations; 1200 g ha−1) applied single or combined with sulfentrazone (600 g ha−1) with four replications, and the experiment was duplicated. The application was performed indoors with an automated sprayer. After application, accumulated rainfall depths (0, 5, 10, 20, 50, and 100 mm) on the treated containers were simulated soon after the herbicide applications, and the percolated waters were subsequently collected for herbicide quantification by chromatography and mass spectrometry (LC-MS/MS). The microencapsulated formulation of clomazone applied single or combined with sulfentrazone enabled the recovery of higher quantity of clomazone (>80%), with the advantage that a large percentage remained encapsulated (>70%), thus decreasing losses and increasing the product efficiency. The 30 mm simulated rainfall efficiently carried the clomazone herbicide when its microencapsulated formulation was applied, whereas its conventional formulation required higher rainfall depths (60 mm). Sulfentrazone was easily carried through the sugarcane straw by the rainfall depths when it was combined with clomazone, regardless of the clomazone formulation. The clomazone formulation affect the percolation dynamics of this herbicide through the sugarcane straw.